2000
DOI: 10.1034/j.1600-0706.2000.880213.x
|View full text |Cite
|
Sign up to set email alerts
|

Does interspecific competition affect territorial distribution of birds? A long‐term study on Siberian Phylloscopus warblers

Abstract: Seven species of Phylloscopus warblers breed in the middle taiga subzone of Central Siberia. We studied their territorial distribution over 18 breeding seasons between 1978 and 1996. 
Phylloscopus inornatus, the most abundant breeding bird species in the study area, breeds in dense clusters of territories. In some habitats, these clusters are very unstable from year to year, providing an excellent opportunity to study the influence of P. inornatus on the territorial distribution of other species. We present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 29 publications
2
33
1
2
Order By: Relevance
“…This conclusion accords well with the results of studies on many other species of vertebrates showing that interspecific interactions affect habitat use (e.g., Bourski and Forstmeier 2000;Tannerfield et al 2002;Robertson 1996;Jaeger 1971). Some of the best examples of such interference effects come from studies on invasive species, or taxa that are expanding their range in anthropogenically modified habitats.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This conclusion accords well with the results of studies on many other species of vertebrates showing that interspecific interactions affect habitat use (e.g., Bourski and Forstmeier 2000;Tannerfield et al 2002;Robertson 1996;Jaeger 1971). Some of the best examples of such interference effects come from studies on invasive species, or taxa that are expanding their range in anthropogenically modified habitats.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, interspecific interference competition of this kind (as opposed to exploitative competition for limited resources) has been documented in a wide range of taxa from most major vertebrate lineages. Direct social interactions between sympatric species influence habitat use in birds (Reed 1982;Robinson and Terborgh 1995;Pearson and Rohwer 1999;Bourski and Forstmeier 2000), mammals (Brown 1970;Grant 1972;Palomares and Caro 1999;Tannerfield et al 2002), fishes (Shulman 1985;Robertson 1996;Bay et al 2001) and amphibians (Inger and Greenberg 1966;Jaeger 1971;Brodman and Jaskula 2002). Remarkably, however, such interactions have attracted much less study in reptiles, especially squamates (lizards and snakes).…”
Section: Introductionmentioning
confidence: 95%
“…In contrast to these findings from Kashmir, our study on territorial spacing in a Central Siberian community of seven species of Phylloscopus warblers (Bourski and Forstmeier 2000) showed that, at this site, the intensity of actual interspecific competition tends to be low. This might be due to breeding communities at northern latitudes being less saturated, as breeding populations of long-distance migrants are often limited by wintering conditions (e.g.…”
Section: Introductioncontrasting
confidence: 70%
“…Thus, we prefer to use the pooled abundance of shrews themselves as a measure of habitat productivity instead of any climatic parameters. A similar approach was used eg in the study of interspecific relationships among Phylloscopus warblers (Bourski and Forstmeier 2000). This approach is also consistent with Tilman's (1982) model, and is supported by reported positive correlations between the density of shrews and the density of their food resources (Holling 1959, Yudin 1962, Butterfield et al 1981, Churchfield et al 1997.…”
Section: Assemblages Of Sorex Shrew In Eurasian Boreal Forests 71supporting
confidence: 65%